The Effectiveness of QR Code-Based Smart Access Library as a Literacy Program in Improving Elementary School Students' Reading Literacy - Irene Maria Wato; Ali Mustadi (FKIP - Universitas Riau, 2026)
Elementary school students' reading literacy skills are still limited to the literal level of understanding due to limited literacy facilities in the school environment. This condition has implications for students' difficulties in understanding vocabulary, identifying main ideas, as well as weakening critical thinking skills and reading interest. This study aims to analyze the effect of using a QR Code-based Smart Access Library as a digital literacy program in improving elementary school students' reading literacy. This study used a pre-experimental design with a one-group pretest–posttest design model. The research subjects consisted of one class of 4th-grade elementary school students who were given treatment in the form of using a QR Code-based Smart Access Library in literacy learning. Data collection was carried out through reading literacy tests given before (pretest) and after treatment (posttest), as well as observations during the learning process. Data analysis used the Wilcoxon Signed-Rank Test. The results showed an Asymp. Sig. (2-tailed) value of 0.000 <0.05, which indicates a significant increase in students' reading literacy skills after the implementation of the QR Code-based Smart Access Library. Thus, the QR Code-based Smart Access Library has the potential to support improving reading literacy of elementary school students.